Carbon Sequestration of Terrestrial Vegetation in China Based on Satellite Remote Sensing Technology - Chen, Jiandong; Li, Zhiwen; Song, Malin; Feng, Ying (Resources, Climate and Sustainable Development, 2025)
XVII, 217 p. 80 illus., 79 illus. in color.